PENGENDALIAN INTERNAL PT. HASJRAT MULTIFINANCE CABANG MANADO DALAM RANGKA MENGENDALIKAN PERSENTASI NON PERFORMING FINANCE (NPF) - Baramuli, Judhistia Putri Judaline; Nangoi, Grace B.; Morasa, Jenny (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
To avoid Non Performance Finance (NPF) problems, the company designs an internal control system. This system is expected to help maximize the performance of the departments responsible for the implementation of the company's operations so as to minimize losses to the company. This study aims to examine how the internal control system implemented by PT. Hasjrat Multifinance so far and what problems occur in the internal control system of PT. Hasjrat Multifinance so that the solution can reduce the company's NPF percentage. This study uses qualitative research methods in the form of case studies, by comparing the implementation of internal control of PT. Hasjrat Multifinance with internal control based on COSO (Committee of Sponsoring Organizations of the Treadway Commission). The results of this study indicate that PT. Hasjrat Multifinance has followed the concepts contained in the Internal Control - Integrated Framework published by COSO, however, in its implementation there are still principles that have not been implemented consistently.